Inhibitory mechanism of KIF3A gene on nasopharyngeal carcinoma stem cells: Inhibitory mechanism of nasopharyngeal carcinoma stem cells - Liu, Rongrong; Li, Te; Zhang, Weitao (Cellular and Molecular Biology, 2023)
To investigate the inhibitory mechanism of the KIF3A gene on nasopharyngeal carcinoma (NPC) tumor stem cells. Set up a blank control group (BCG), NPC group, and KIF3A silence (si-KIF3A) group. The BCG cells were nasopharyngeal normal epithelial cell line NP69, without any treatment, and were cultured routinely; The NPC group cells are human NPC cell line CNE2 cells, which are not subjected to any treatment and are cultured routinely; si-KIF3A group cells were cultured in the offspring of human NPC cell line CNE2 infected with Lentivirus knockdown KIF3A gene. CCK8 was used to detect the cell proliferation ability, Western blot and qPCR were used to detect protein and related mRNA expression, while cell migration and invasion were detected using Transwell. The KIF3A protein and mRNA in the NPC group were higher than those in the BCG (P<0.05), while those in the si-KIF3A group cells were lower compared to BCG cells (P<0.05). The cell proliferation, migration and invasion activity in the si-KIF3A group were reduced than those in BCG (P<0.05). Si-KIF3A group cells HIF-1, NF-κB was reduced than that of BCG (P<0.05). The expression level of HIF-1, NF-κB protein in si-KIF3A group cells was reduced compared to BCG cells (P<0.05). Knocking down the KIF3A gene can reduce the vitality of NPC stem cells, and inhibit the malignant phenotype of NPC stem cells, via inhibiting HIF-1 and NF-κB expression.